1990
DOI: 10.1210/mend-4-6-886
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Pattern of Proopiomelanocortin Gene Expression in the Arcuate Nucleus of Proestrous, Ovariectomized, and Steroid-Treated Rats: A Possible Role in Cyclic Luteinizing Hormone Secretion

Abstract: Opiate peptides are thought to modulate the pattern of LH release in female rats. We tested the hypothesis that changes in proopiomelanocortin (POMC) gene expression occur in proestrous (PRO) and ovariectomized (OVX) steroid-treated rats which may explain their unique patterns of LH secretion. Using in situ hybridization, we examined whether diurnal changes in POMC gene expression occur in the arcuate nucleus. Four groups of rats were used in this study. 1) PRO rats were used after exhibiting at least two cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 38 publications
4
64
0
Order By: Relevance
“…In terms of the latter, it is clear that prolonged estrogen exposure decreases ␤END mRNA and peptide expression within the arcuate nucleus (380,382,383). However, ␤END peptide and mRNA analyses also show that a significant diurnal rhythm occurs within the ␤END neurons; ␤END expression is lowest in the afternoon, and this diurnal rhythm is only evident in the presence of estrogen (381,384,385). Hence, the arcuate ␤END neurons may be an additional site at which estrogen and circadian inputs are integrated before transmission to the GnRH neurons in the rat.…”
Section: June 1998 Estrogen Inputs To Gnrh Neurons 315mentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the latter, it is clear that prolonged estrogen exposure decreases ␤END mRNA and peptide expression within the arcuate nucleus (380,382,383). However, ␤END peptide and mRNA analyses also show that a significant diurnal rhythm occurs within the ␤END neurons; ␤END expression is lowest in the afternoon, and this diurnal rhythm is only evident in the presence of estrogen (381,384,385). Hence, the arcuate ␤END neurons may be an additional site at which estrogen and circadian inputs are integrated before transmission to the GnRH neurons in the rat.…”
Section: June 1998 Estrogen Inputs To Gnrh Neurons 315mentioning
confidence: 99%
“…However, the marked increase in progesterone concentrations that follows the onset of the LH surge exerts an opposite effect to estrogen on these cells and increases ␤END mRNA levels (381,383). This is suggested to be the neural mechanism through which progesterone inhibits the occurrence of a further estrogen-induced LH surge on estrus (386,389).…”
Section: June 1998 Estrogen Inputs To Gnrh Neurons 315mentioning
confidence: 99%
“…Animals housed under this LD cycle show a proestrous or estrogen-induced surge of LH between 1500 -1800 h (33). Estrous cyclicity was monitored using vaginal cytology.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…Sections were thaw mounted onto slides and stored at Ϫ70 C until they were processed for in situ hybridization following a previously established protocol (33). A total of 52 sections (26 slides) containing the SCN were collected from each animal.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…For instance, estrogens may modify the production and the release of endogenous opioids [5], as well as the binding characteristics of brain opioid receptors [6]. Findings from this and other laboratories have shown that, in female rats, the phyisological fluctuations of estrogens and progesterone during the estrous cycle, as well as during pregnancy, are accompanied by modifications of the concentration of µ opioid receptors in the brain [7, 8, 9, 10].…”
Section: Introductionmentioning
confidence: 99%